Gamification's Effectiveness in Online English Teaching in the Pandemic Era - Muhamad Sofian Hadi; Nabil irbah Athallah (Universitas Cokroaminoto Palopo, 2021)
The current study aimed to describe students' perceptions of their English mastery, and the media used by the researcher is a gamification platform (Quizizz). The study used a qualitative approach with a descriptive approach, and the instrument was a questionnaire. The participants were given a total of ten questions. There are 30 people who have already completed the questionnaire. According to the results of a questionnaire administered to 30 students, they have a favorable opinion of Gamification platforms for improving their English proficiency. Based on the overall data presented in the previous sections, it was clear that the English mastery material that was equipped with a Gamification platform as a media to improve English mastery received a positive perception and positive comments